New species of Haplometroides (Digenea: Plagiorchiidae) from Phalotris nasutus (Gomes, 1915) (Serpentes, Colubridae) - Da Silva, Reinaldo José [UNESP]; Ferreira, Vanda Lúcia [UNESP]; Strüssmann, Christine [UNESP] (American Society of Parasitologists, 2007)
A new species of Haplometroides (Digenea, Plagiorchiidae) is described from a specimen of Phalotris nasutus (Gomes, 1915) (Serpentes, Colubridae). The host snake was obtained in the municipality of Corumbá, Mato Grosso do Sul State, Brazil. Trematodes were recovered from esophagus, stomach, and small intestine of the host. The main characteristic of the new species is the vitellaria, which is intercecal, cecal, and extracecal in the preacetabular region. A key for identification of the species in Haplometroides is proposed. © American Society of Parasitologists 2007.
Keywords: flatworm; host; identification key; new species; snake; Brazil; esophagus; Haplometroides; morphology; nonhuman; Phalotris nasutus; Plagiorchiidae; small intestine; stomach; taxonomy; trematode; Animals; Colubridae; Esophagus; Gastrointestinal Diseases; Intestine, Small; Male; Stomach; Trematoda; Trematode Infections; Corumba; Mato Grosso do Sul; South America; Digenea (flukes); Serpentes; Vitellaria